(The Narratives of Asma Bint Yazid Al-Ansari in Sunan Abi Dawood - collection and study) (Islamic Sciences Journal, 2023)
This research aims to clarify the status of the great companion Asmaa bint Yazid (may God be pleased with her). Because she was defending them and asking about their rights, she narrated from the Messenger of God (may God bless him and grant him peace) several hadiths, and she was one of those who were keen to transmit the Sunnah of the Prophet (peace and blessings of God be upon him) and for that I chose to have my research titled (The Narratives of Asma Bint Yazid Al-Ansariah). In Sunan Abi Dawood - collection and study).
Keywords: Narratives, Al-Ansariyyah, the hadith of the Greatest Name of God, the kit, the Ghail, the works, the dress, the adornment.